2020
DOI: 10.1002/jsfa.10640
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride absorption, transportation and tolerance mechanism in Camellia sinensis, and its bioavailability and health risk assessment: a systematic review

Abstract: Tea is the one of the most popular non-alcoholic caffeinated beverages in the world. Tea is produced from the tea plant (Camellia sinensis (L.) O. Kuntze), which is known to accumulate fluoride. This article systematically analyzes the literature concerning fluoride absorption, transportation and fluoride tolerance mechanisms in tea plants. Fluoride bioavailability and exposure levels in tea infusions are also reviewed. The circulation of fluoride within the tea plantation ecosystems is in a positive equilibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 106 publications
(205 reference statements)
0
3
0
Order By: Relevance
“…The majority of F is quickly transferred as F/F-Al complexes to the leaf cell walls and vacuole across the xylem. The results suggest that tea plants detoxify F and aluminum (Al) simultaneously through cell wall accumulation, vacuole compartmentalization, and F-Al complexes, which may be a mechanism of F tolerance that enables tea to withstand higher F concentrations than most plants (Peng et al, 2020;Luo et al, 2022).…”
Section: Figurementioning
confidence: 99%
“…The majority of F is quickly transferred as F/F-Al complexes to the leaf cell walls and vacuole across the xylem. The results suggest that tea plants detoxify F and aluminum (Al) simultaneously through cell wall accumulation, vacuole compartmentalization, and F-Al complexes, which may be a mechanism of F tolerance that enables tea to withstand higher F concentrations than most plants (Peng et al, 2020;Luo et al, 2022).…”
Section: Figurementioning
confidence: 99%
“…From the study of Zhang et al [190], it was observed that anion blockers inhibited the uptake of F − ions in tea plants (Camellia sinensis), and it was suggested that anion channels might play an essential role in the absorption of F − ions for the tea plants. Tea plants tolerate higher fluoride levels than other plants [218]. It was found that most of the F − ions uptaken by the roots of tea plants were readily transported to the leaves through the xylem [190].…”
Section: Fluoride Uptake and Bioaccumulation In Plants And Foodsmentioning
confidence: 99%
“…Fluorine is a major groundwater and soil pollutant detected across major rice cultivating nations, such as China, India, Pakistan, Bangladesh, Indonesia and Myanmar (Mukherjee and Singh 2020). Alarming level of groundwater fluoride pollution occurs due to unplanned mining of fluoride-rich minerals, such as cryolite, appatite, etc., climatic weathering and edaphic ion-exchange processes (Peng et al 2020). Susheela (1999) reported fluoride level to be as high as 48 mg L −1 in the groundwater across Indian states.…”
Section: Introductionmentioning
confidence: 99%